Gestão de custos na administração pública: um estudo de caso do Departamento de Água e Esgoto (DMAE) do município de Porto Alegre - RS - Lopes, Marco Antônio Mascarenhas de Souza (2024)
Cost management in public administration has become increasingly vital, driven by the need for continuous improvement in public spending management, managerial control, transparency, and support for decision-making. The pursuit of quality and efficiency within the organizational structures is a fundamental responsibility of managers, who must adopt processes to prevent waste and ensure greater social profitability. In recent years, numerous regulations and initiatives have emerged regarding the implementation of cost control systems in the public sector. Cost management enables the monitoring, evaluation, transparency, and efficiency of a wide range of public services that the administration must provide, including the essential service of basic sanitation. In this context, the objective of this study was to analyze the cost system of the Municipal Department of Water and Sewage (DMAE) of Porto Alegre – RS, a municipal authority responsible for providing water supply, sewage collection, and treatment services, which has implemented a cost management system. The research conducted within this administrative structure focused on its activities and cost drivers. Using the information generated through the activity-based costing (ABC) method, it becomes possible to measure costs and propose solutions, offering a tool that is both useful for managers and reliable for society. The method helps identify areas for improvement and ensures accuracy in accounting information. This research combines quantitative and qualitative approaches. It is exploratory, and bibliographic in nature, incorporating a case study and a questionnaire composed of questions aligned with the research objectives. The results indicate that the implementation of the DMAE cost system has led to significant advancements in data generation, aiding the municipality in pricing services, reducing costs, improving the monetary estimation of water distribution losses, refining the estimation of cross-subsidies for services, and fulfilling its operational mandates. Cost management in Public Administration plays a critical role in enhancing management control, optimizing public spending, ensuring transparency, and supporting decision-making by managers.